Cyprinid fishes of the genus Neolissochilus in Peninsular Malaysia - Khaironizam, M. Z.; Akaria-Ismail, M.; Armbruster, Jonathan W. (Zootaxa, 2015)
Meristic, morphometric and distributional patterns of cyprinid fishes of the genus Neolissochilus found in Peninsular Malaysia are presented. Based on the current concept of Neolissochilus, only two species are present: N. soroides and N. hendersoni. Neolissochilus hendersoni differs from N. soroides by having lower scale and gill raker counts. Neolissochilus soroides has three mouth types (normal with a rounded snout, snout with a truncate edge, and lobe with a comparatively thick lower lip). A PCA of log-transformed measurements did not reveal significant differences between N. hendersoni and N. soroides, or between any of the morphotypes of N. soroides; however, a CVA of log-transformed measurements successfully classified 87.1% of all specimens. Removing body size by running a CVA on all of the principal components except PC1 (which was correlated with length) only slightly decreased the successful classification rate to 86.1%. Differences in morphometrics were as great between the three morphotypes of N. soroides as between any of the morphotypes and N. hendersoni suggesting that the morphotypes should be examined in greater detail with genetic tools. The PCA of morphometrics revealed separate clouds for N. hendersoni and N. soroides, but no differences between the N. soroides morphotypes. This study revealed that N. hendersoni is recorded for the first time in the mainland area of Peninsular Malaysia. Other nominal species of Neolissochilus reported to occur in the river systems of Peninsular Malaysia are discussed. Lissochilus tweediei Herre in Herre & Myers 1937 and Tor soro Bishop 1973 are synonyms of Neolissochilus soroides.